Slicing of extended finite state machines - Atchuta, Kaushik (Kansas State University, 2014)
An EFSM (Extended Finite State Machine) is a tuple (S, T, E, V) where S is a finite set of states, T is a finite set of transitions, E is a finite set of events, and V is a finite set of variables. Every transition t in T has a source state and a target state, both in S. There is a need to develop a GUI which aids in building such machines and simulating them so that a slicing algorithm can be implemented on such graphs. This was the main idea of Dr. Torben Amtoft, who has actually written the slicing algorithm and wanted this to be implemented in code. The project aims at implementing a GUI which is effective to simulate and build the graph with minimum user effort. Poor design often fails to attract users. So, the initial effort is to build a simple and effective GUI which serves the purpose of taking input from the user, building graphs and simulating it. The scope of this project is to build and implement an interface so that the users can do the following in an effective way:  Input a specification of an EFSM  Store and later retrieve EFSMs  Displaying an EFSM in a graphical form  Simulating the EFSM  Modify an EFSM  Implement the slicing algorithm All the above mentioned features must be integrated into the GUI and it should only fail if the input specification is wrong.
Keywords: Finite state machines; Slicing of finite state machines; simulating finite state machines; Building finite state machines; Finite automata; Computer Science (0984)